Influence of the sodium content on the reactivity of carbon anodes - Batista,Jefferson dos Santos (2008)
Spent anodes, denominated butts in the aluminum industry, are recycled as part of the raw material used to produce new anodes. The fragmentation of the butt generates some sodium-rich powder, which is captured and included in the recycled material. This paper evaluates the influence of sodium content on anode reactivity. Six formulations with 0 to 25% butt powder were used. An average increase of 48 ppm of sodium from one to another formulation caused average increments of 3.38 and 2.72% for air and CO2 reactivity, respectively. The quality-related figures varied from 1.34 to 1.12 for CO2 and from 1.10 to 0.62 for air, showing quality loss in higher sodium content and higher impact on air reactivity. The Fischer formula predicted a carbon specific consumption of - 48.47 kg.t-1 Al for baked carbon anodes with 127 ppm to 367 ppm of sodium content, showing that the sodium can cause relevant carbon losses and increase costs of the aluminum production.